PENGARUH PERPUTARAN MODAL KERJA TERHADAP LABA BERSIH PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2019 (JAPB, 2022)
This study aims to determine: 1) Is there any effect of working capital turnover on the net income of automotive companies listed on the Indonesia Stock Exchange in 2017-2019. 2) How big is the influence of working capital turnover on the net profit of automotive companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study is 14 automotive companies listed on the Indonesian stock exchange that meet the criteria and the number of samples is 42 observations. This study uses a quantitative approach in which information or data is presented in the form of numbers. Data collection is done by documentation and literature study. These data are then processed with the SPSS application, and interpreted in such a way as to reach a conclusion. Turnover of working capital shows the effectiveness of the use of working capital in generating sales which shows the company's ability to generate profits in relation to sales. In other words, it can be interpreted that if the turnover of the company's working capital is high, it is certain that the sales generated will also be high, which will have the potential to increase the profits earned by the company. Based on the results of the study it can be concluded that there is an effect of working capital turnover on net income. That 7.8% variation in net profit variable is influenced by variations in working capital turnover variable. Meanwhile, the remaining 92.2% of the variation in the net profit variable can be influenced by other variables not included in this study. Keywords: Working capital turnover, net profit, automotive companies, IDX